2013
DOI: 10.1002/jgrc.20286
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and sources of organic matter in surface marine sediments across the North American Arctic margin

Abstract: [1] As part of the International Polar Year research program, we conducted a survey of surface marine sediments from box cores along a section extending from the Bering Sea to Davis Strait via the Canadian Archipelago. We used bulk elemental and isotopic compositions, together with biomarkers and principal components analysis, to elucidate the distribution of marine and terrestrial organic matter in different regions of the North American Arctic margin. Marked regional contrasts were observed in organic carbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
92
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(102 citation statements)
references
References 128 publications
9
92
1
Order By: Relevance
“…Lignin is an essential component in the cell walls of vascular plants (Higuchi, 1971), while cutin is a lipid polyester, which forms a protective wax layer on the epidermal cells of leaves and needles with other lipids (e.g., Kunst and Samuels, 2003). These compounds have been demonstrated to be useful in studying terrestrial OC in the Arctic (e.g., Amon et al, 2012;Bröder et al, 2016a;Goñi et al, 2013;Tesi et al, 2014). Both lignin and cutin fluxes show a similar trend with the highest fluxes at the bottom of the core (∼ 9500 cal yrs BP) indicating a high proportion of terrestrial organic matter (Fig.…”
Section: Sediment Grain Size Stable Carbon Isotopes and Biomarker Comentioning
confidence: 99%
See 1 more Smart Citation
“…Lignin is an essential component in the cell walls of vascular plants (Higuchi, 1971), while cutin is a lipid polyester, which forms a protective wax layer on the epidermal cells of leaves and needles with other lipids (e.g., Kunst and Samuels, 2003). These compounds have been demonstrated to be useful in studying terrestrial OC in the Arctic (e.g., Amon et al, 2012;Bröder et al, 2016a;Goñi et al, 2013;Tesi et al, 2014). Both lignin and cutin fluxes show a similar trend with the highest fluxes at the bottom of the core (∼ 9500 cal yrs BP) indicating a high proportion of terrestrial organic matter (Fig.…”
Section: Sediment Grain Size Stable Carbon Isotopes and Biomarker Comentioning
confidence: 99%
“…Coastal erosion can be further intensified with warming-enhanced processes like loss of sea ice cover, increasing frequency of storms, degradation of icebonded coasts and sea level rise (Barnhart et al, 2014;Jones et al, 2009;Stein and Macdonald, 2004). The largest rivers directly emptying into the ESS are Indigirka and Kolyma with suspended matter discharge of 11.1 × 10 12 g yr −1 and 123 ± 19 × 10 9 g yr −1 (Gordeev, 2006;McClelland et al, 2016, respectively) and an input also from the Lena River. The Lena River drains into the Laptev Sea, but its exported terrestrial OC is also transferred to the ESS via the Siberian Coastal Current (e.g., Alling et al, 2012;.…”
Section: Introductionmentioning
confidence: 99%
“…The researches of MacDonald and Pedersen (1991) showed that most of OC settled in western Canadian shelf was from marine production. In addition, many studies on OC source apportionment have also been carried out in the Bering (de Haas et al, 2002), the Chukchi shelves (Goñi et al, 2013), the Yellow Sea and East China Sea continental shelf (Yang et al, 2012). On the other hand, many studies have found that TIC accounted for a large proportion of TC burial fluxes in some waters, such as mud area of the East China Sea (64.1%-87.6%) (Guo et al, 1999), western Nansha Islands (about 50%) (Gao et al, 2008a), western Taiwan Strait (>90%) (Ye et al, 2011), eastern margins of the Arabian Sea (>90%) (Bhushan et al, 2001), European Goban Spur continental margin (about 70%) (Van Weering et al, 1998).…”
Section: Introductionmentioning
confidence: 98%
“…However, the westward extent of the Mackenzie outflow is variable over time, and allochthonous nutrient and terrestrial carbon input from the numerous smaller rivers can probably be as important, at least to nearshore (<20 m depth) Alaska Beaufort food webs (Dunton et al 2006). Coastal erosion also contributes large amounts of terrestrially derived carbon to the Alaska portion of the Beaufort shelf (Goñi et al 2013). Although the importance of terrestrial carbon subsidies, including those from the Mackenzie River, to nearshore benthic food webs of the Beaufort Sea has been established (e.g.…”
Section: Introductionmentioning
confidence: 99%